A new corpus of geolocated ASR transcripts from Germany. - Coats, Steven (Language Resources & Evaluation, 2025)
This report describes the Corpus of German Speech (CoGS), a 56-million-word corpus of automatic speech recognition transcripts from YouTube channels of local government entities in Germany. Transcripts have been annotated with latitude and longitude coordinates, making the resource potentially useful for geospatial analyses of lexical, morpho-syntactic, and pragmatic variation; this is exemplified with an exploratory geospatial analysis of grammatical variation in the encoding of past temporal reference. Additional corpus metadata include video identifiers and timestamps on individual word tokens, making it possible to search for specific discourse content or utterance sequences in the corpus and download the underlying video and audio from the web, using open-source tools. The discourse content of the transcripts in CoGS touches upon a wide range of topics, making the resource potentially interesting as a data source for research in digital humanities and social science. The report also briefly discusses the permissibility of reuse of data sourced from German municipalities for corpus-building purposes in the context of EU, German, and American law, which clearly authorize such a use case.